PENGGUNAAN METODOLOGI DALAM PENETAPAN FATWA MURABAHAH DARI SUDUT PANDANG USHUL FIQH - Faikoh, Iik; Silahuddin, Muhammad (An Nawawi, 2023)
This study aims to find out the methodology for establishing DSN-MUI fatwas in the perspective of ushul fiqh, especially regarding fatwas on murabaha. Methodology is a process that is well established, customary, logical practice, or determined or systematic to achieve certain goals with accuracy or efficiency, usually in a fixed sequence of steps. . While methodology is the science of methods (systematic presentation) or descriptions of methods. This study uses a qualitative method. Qualitative research was used to analyze the methodology for determining the DSN-MUI murabaha fatwa from the perspective of ushul fiqh. The types of data and research materials come from primary and secondary data. Primary data comes from fatwa documents and interviews while secondary data comes from literature. The collection technique in this study was by interviewing respondents to obtain accurate and reliable information. The results of the study show that the DSN-MUI in establishing fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah is the istislahi method. With this method, the DSN-MUI identifies murabaha transaction problems that do not have specific texts as a reference. In using this istislahi method, DSN collects general verses.